Associação entre a aptidão física e o tipo e frequência de exercício em idosos participantes no programa: "Com exercício físico, mais e melhores anos" - Ana Isabel Faria Cardoso (2016)
Aging is a phenomenon with multiple impacts on social environment that concerns lots of researchers. For example, physical trainers/sports' professionals try to adjust physical exercises to the elderly's physical capacities. To guarantee that elderly have physical fitness to execute daily tasks. This dissertation focuses on the project developed in Vila Nova de Famalicão ("Com Exercício Físico: Mais e Melhores Anos"), which attemps to improve the functional physical fitness of the elderly. It is divided in two parts: the first one compares the results obtained with that published in 2002 by Jones and Rikli and analyses the physical composition of the participants and their permanence in the program. The second part explores some data collected thru a sample survey (with 71 respondents) with the aim of characteriz the elderly of the city. We verified that the time in the program and the weekly frequency do not affect the average results obtained in each fitness test. However, we have concluded that the elderly with higher BMI have lower scores in the fitness tests. In the analysis of the type of classes and modalities chosen by the elderly, one can conclude that the results are higher than the recommended by Jones and Rikli in the assessment of the strength (besides the age and gender of the individual). Nevertheless, it was possible to verify that one of the components of flexibility faces some execution difficulties. Finally, we have concluded that the number of diseases does not affect physical fitness and that an increase in the number of diseases is associated with a better perception of health. Regarding the residential area (city or suburbia), there are only statistically significant differences in test 1. Also, living closer to recreational places has not a significant impact in the fitness test results.